2011
DOI: 10.3844/ajabssp.2011.214.220
|View full text |Cite
|
Sign up to set email alerts
|

Leaf Chlorophyll Fluorescence and Gas Exchange Response to Different Light Levels in <i>Platycerium bifurcatum<i/>

Abstract: Problem statement: Platycerium bifurcatum (Cav.) C. Chr. is epiphytes which lives in forest canopy and commonly used for its ornamental value. In these environments, they were always exposed to many types of stresses such as high light intensity. Light intensity plays an important role in affecting plant's physiological performance. Therefore, the purpose of this study was to investigate physiological responses of P. bifurcatum to light stress. Approach: In this study, P. bifurcatum were grown under four diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…The previous research on P. bifurcatum physiology was primarily associated with ensuring proper growing conditions and micropropagation methods of these ornamental plants (Aspiras et al 2010, Liao andWu 2011). In addition, drought stress response was investigated by Rut et al (2003), and the subject of intense light stress was studied by Sanusi et al (2011). However, there is still a lack of information on the response of the photosynthetic apparatus to the sudden increase in light intensity, e.g., after tree logging in a large forest area.…”
Section: Methodsmentioning
confidence: 99%
“…The previous research on P. bifurcatum physiology was primarily associated with ensuring proper growing conditions and micropropagation methods of these ornamental plants (Aspiras et al 2010, Liao andWu 2011). In addition, drought stress response was investigated by Rut et al (2003), and the subject of intense light stress was studied by Sanusi et al (2011). However, there is still a lack of information on the response of the photosynthetic apparatus to the sudden increase in light intensity, e.g., after tree logging in a large forest area.…”
Section: Methodsmentioning
confidence: 99%
“…A significant decrease in the PSII photochemical efficiency was recorded in plant leaves exposed to H-R/FR after 3 months of growth compared with that observed after 1 month (Table 1). Sanusi et al (2011) demonstrated that longer exposure of P. bifurcatum to intense sunlight above 200 lmol (quantum) m -2 s -1 contributed to the reduction of F V /F M , although it was not yet a sign of photoinhibition, which is diagnosed only at the PAR intensity of 1500 lmol (quantum) m -2 s -1 . This allowed to conclude that the plants growing under H-R/ FR responded to the information about a higher light energy dose.…”
Section: Photosynthetic Efficiency Of Leavesmentioning
confidence: 99%
“…Physiological studies conducted so far have been mainly limited to determination of the response of this plant to drought stress and a description of micropropagation methods for commercial purposes (Rut et al 2003;Aspiras 2010, Liao andWu 2011). In recent years, research has been initiated on the effects of light intensity on the functioning of photosynthetic apparatus of P. bifurcatum (Sanusi et al 2011), which natural habitats are increasingly exposed to stress radiation. It is associated with increased anthropogenic pressure in the areas of its occurrence, particularly with rainforest deforestation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…F is a value of light-adapted steady state fluorescence. Fv/Fm is a value of PSII maximum quantum yield after dark adaptation and is an informative criteria to study induced changes in PSII (Sanusi et al, 2011). Y(II) is a value of PSII effective quantum yield.…”
Section: Chlorophyll Fluorescence Measurementsmentioning
confidence: 99%